Logic and philosophy : - Hausman, Alan (Thomson Wadsworth, 2007)
This was the text book used in a logic class I took. The book covers truth functions, truth tables, conditional proofs, indirect proofs, predicate logic, truth trees, syllogistic logic, inductive logic, axiomatic systems and a few other lesser used logical systems. Each section is explained clearly and with great attention to detail. As it is a text-book, every chapter ends with several problems for the reader to solve. There are lots and lots of examples that help to hammer the concept home if the reader has become stuck on some of the more difficult passages. This book is a great teacher and is an excellent resource for anyone who is interested in logic.